213 Synergy between Endothelial Mediators and P2Y12 Receptor Blockade as a Potential Determinant in Tailoring Anti-Platelet Therapy. (6th June 2015) - Knowles, Rebecca; Chan, Melissa; Lundberg, Martina; Kirkby, Nicholas; Shih, Chih-Chin; Armstrong, Paul; Hayman, Melissa; Vojnovic, Ivana; Tucker, Arthur; Warner, Timothy; Timmis, Adam
Abstract : Introduction: Following ACS or PCI, P2Y12 receptor blockers such as clopidogrel or prasugrel are standardly prescribed alongside aspirin as dual anti-platelet therapy in a "one size fits all" approach, however recurrent thrombotic events occur. Despite the logical hypothesis that thrombotic risk should be associated with level of P2Y12 platelet inhibition, randomised control trials have repeatedly failed to show any clinical benefit of guiding anti-platelet therapy by platelet function tests (PFT). Whilst traditional PFT measure reactivity to ADP, they crucially ignore that P2Y12 receptor antagonists also produce powerful anti-thrombotic effects by potentiating the actions of the inhibitory endothelial mediators prostacyclin (PGI2) and nitric oxide (NO). Methods: In vitro, IC50 curves produced from light transmission aggregation (LTA) traces for PGI2, NO and prasugrel active metabolite (PAM: 3 μM) were used to generate isobolograms. Ex vivo, healthy male volunteers (n = 8 each) received either prasugrel (10 mg) or aspirin (75 mg) for 7 days. Platelet-rich plasma (PRP) was obtained by centrifugation before and after treatment. Platelet responses to TRAP-6 amide (25 μM) or collagen (4 μg/ml) in the presence of PGI2 (1 nM) and/or the NO donor, DEA/NONOate (100 nM), or vehicle, were assessed by LTA, p-selectin binding by flow cytometry, and downstream cyclic nucleotide and VASP phosphorylation by immunoassay. Results: Isobolographic analysis of in vitro studies showed P2Y12 blockade powerfully enhanced the synergy between NO and PGI2 (10 fold for TRAP-6). Ex-vivo platelet aggregation responses to TRAP-6 were unaffected by the addition of PGI2+NO prior to therapy. Aspirin monotherapy produced minimal inhibition of TRAP-6, though these became stronger in the presence of PGI2+NO (58%±8 to 28%±9; p < 0.05). Inhibitory effects were observed with prasugrel in the presence of PGI2 and NO individually (control, 63 ± 3%; PGI2, 43 ± 6%; NO, 50 ± 5%), and these became much greater with the combination (PGI2+NO, 7%±3). P-selectin expression was reduced from pre-treatment (vehicle, 32 ± 6%) to (PGI2+NO, 11 ± 4%) post aspirin, and from (vehicle, 25 ± 6%) to (PGI2+NO, 2 ± 4%) following prasugrel. cAMP levels increased with PGI2+NO in the aspirin group (0.97 ± 0.06 vs. 1.50 ± 0.19) compared to (1.41 ± 0.07 vs. 3.4 ± 0.58) in the prasugrel group. Conclusions: PGI2 and NO synergise with P2Y12 blockade to cause powerful platelet inhibition suggesting that an individual's endothelial function and production of NO and PGI2 are central determents of the anti-thrombotic protection from P2Y12 receptor blocker therapy. Whilst a therapeutic window of platelet reactivity is an attractive concept our research suggests that endothelial function testing alongside PFT would permit better risk stratification. Our research also suggests therapeutically that enhancing endothelial-derived mediators or optimising downstream cyclic nucleotide signalling could reduce both thrombotic and bleeding risk.